1973
DOI: 10.1073/pnas.70.3.762
|View full text |Cite
|
Sign up to set email alerts
|

Photoreversible Conductance Changes Induced by Phytochrome in Model Lipid Membranes

Abstract: The plant protein phytochrome induces photoreversible conductance changes when added to a black lipid membrane made from oxidized cholesterol. The conductance of the phytochrome-modified membrane is increased by red-light illumination but is decreased by illumination with far-red light. Denatured phytochrome does not affect the conductance of the model membrane.Phytochrome is a widely distributed plant chromoprotein that mediates many developmental changes triggered by light (1, 2). It has two spectrally diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Many other phytochrome-mediated physiological responses involve changes in membrane associated properties (21). In model membrane systems phytochrome modulates membrane conductivity (20). As a speculative hypothesis to stimulate further research we propose that the primary mechanism of phytochrome action is the formation of a Pfr-membrane steroid complex which acts as a native channel-forming quasi-ionophore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other phytochrome-mediated physiological responses involve changes in membrane associated properties (21). In model membrane systems phytochrome modulates membrane conductivity (20). As a speculative hypothesis to stimulate further research we propose that the primary mechanism of phytochrome action is the formation of a Pfr-membrane steroid complex which acts as a native channel-forming quasi-ionophore.…”
Section: Resultsmentioning
confidence: 99%
“…The failure of Triton X-100 to release attached phytochrome suggests that the polar head groups of phospholipids do not play a direct role (17). Roux and Yguerabide (20) and later Roux (19) suggested that association ofphytochrome with artificial membranes takes place only when the steroid cholesterol is included, no association occurring with membranes composed entirely of phosphatidyl choline or phosphatidylethanolamine. Steroids have also been implicated in the photoperiodic induction of flowering in Xanthium by Mitra and Sen (13) using filipin ( a polyene antibiotic) which affects membrane properties in different biological systems by its specific interaction with steroids (9,10,14,22).…”
mentioning
confidence: 99%
“…The postulate that phytochrome works in membranes has also been supported by direct demonstration of phytochrome incorporation into "black lipid" model membranes containing oxidized cholesterol (119). The resistance of such membranes change markedly with alternating R and FR, indicating that conformational changes of the phytochrome alters membrane structure.…”
Section: Tirelymentioning
confidence: 63%
“…A conformational change (1) in the structure of phytochrome (Pfr) is known to produce a rapid positive potential in the plasma membrane (2). Phytochrome has been reported to cause a fast change in the permeability of artificial membranes (9). A rise in the positive potential of the membrane would then increase the rate of flow of fluorescein, auxin, and other negatively charged ions in receptor cells.…”
Section: Discussionmentioning
confidence: 99%